A Literature Review of Sukku (Zingiber officinale) Related to Its Medicine in Traditional Medicine in Sri Lanka - Janani, K.; Desigan, Y.; Nushrath Roshana, M. (Middle East Journal of Applied Science & Technology, 2020)
The Sri Lankan traditional medicine is a combination of indigenous medicine of the country and Ayurveda received from India, siddha medicine from south India and Unani from middle east. Sukku (Zingiber officinale) is an herbal origin under the family of Zingiberacea. It is a perennial herb with horizontal rhizome occurred in branched pieces. Its phytochemicals actions help to cure many diseases fever, GIT disorders, kerdpa vaayu and headache etc. Sukku is one of the ingredients in most of the prescribed drugs by doctors in Ayurveda, siddha government hospital in Sri Lanka. Therefore, we selected this herb to literature review related to its medicines in traditional medicine. 270 Sukku related prepared medicines are collected from 48 references. From the review 77% were internal medicines and 23% were external medicines. From the internal medicines kudineer has highest numbers (60), kalgam and melugu have least numbers (2). From the external medicines 72% were oils, 12% were maathirai, 2% anchanam, 8% were patru, 3% were pugai and poochu. From this review 115 were cured Gastro intestinal tract disorders, 56 were fever, 26 were vaatham, 23 respiratory diseases, 17 were pittam and 15 were eye diseases etc. This literature review provides useful documented evidences related its medicines. There is need further laboratory study about this herb in future.
Keywords: Indication; Prepared medicines; Sukku; Traditional medicine